Life table and demographic parameters of Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) reared on wheat germ and sweet potato based artificial diets - Salmah Mohamed; Wan Nor Safikal Wan Ahmad; Mohammad Hailmi Sajili; Norhayati Ngah; Nur Athiqah Md Yusof; Marina Roseli (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The mass production of insects such as fruit flies are commonly use artificial diets due to the easier management in the laboratory compare to using natural diets. However, some commercially imported artificial diets such as wheat germ are quite expensive and not cost effective. Thus, other alternative sources of artificial diets using local ingredients such as sweet potatoes is required as it is more economical compared to wheat germ. Therefore, this study aimed to compare the life table and demographic parameters of Bactrocera dorsalis reared on wheat germ (WG) and orange sweet potato (SP) based artificial diet. We used 3-cohorts of 100 of B. dorsalis eggs were reared on WG and SP diet, respectively and the fly’s survivorship and fecundity were recorded daily in the laboratory. Larval and pupal duration, pupae weight, adult emergence and longevity, pre-oviposition and oviposition period were also recorded. Results showed that the age-specific survival (lx) of B. dorsalis eggs reared on WG and SP diet successfully reached to adults’ stage at 62.33% and 57.67%, respectively. The highest mortality of B. dorsalis stage recorded was at first instar larvae with K-value of 0.266 (WG) and 0.264 (SP), and the pattern of survivorship curves for both diets fall in Type III. Age-specific fecundity (mx) for both diets showed the earliest egg laying was on day 37. There was no significant difference (P>0.05) of B. dorsalis larval duration, pupal duration, pupal weight, adult emergence, adult longevity, pre-oviposition, oviposition period and fecundity for both diets. However, the larval survival and the daily eggs produced for the fly reared on wheat germ-based diet were significantly higher (P<0.05) compared to sweet potato-based diets. In conclusion, B. dorsalis reared on orange sweet potato-based diet showed the similar potential as reared on wheat germ-based diet due to parallel biological parameters results.